Effectiveness of the Nutrition Education Program in Increasing Awareness of Balanced Eating Patterns in Elementary Schools - Vika Fransisca (Al Makki Health Informatics Journal, 2024)
The increasing prevalence of malnutrition and diet-related health issues among children emphasizes the urgent need for effective nutrition education. This study evaluates the effectiveness of a tailored nutrition education program in increasing awareness of balanced eating patterns among elementary school students in Indonesia. Using a qualitative research design, data were collected through semi-structured interviews, focus group discussions, and observations involving 20 students and their teachers. The findings reveal significant improvements in students' knowledge and attitudes toward balanced eating, highlighting the effectiveness of interactive learning methods and culturally relevant content. Parental involvement emerged as a critical factor in reinforcing the program's lessons. Challenges such as financial constraints and varying levels of parental support were noted, suggesting the need for community-level interventions. The results align with social cognitive theory, emphasizing observational learning and environmental influences. This study underscores the importance of integrating nutrition education into school curriculums and provides a replicable model for similar interventions. Future research should explore the long-term impacts and scalability of such programs.